2014
DOI: 10.1371/journal.pone.0098797
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Complications of Total En Bloc Spondylectomy: Adverse Effects of Preoperative Irradiation

Abstract: BackgroundTotal en bloc spondylectomy (TES) is associated with a high complication rate because it is technically demanding and involves patients compromised by cancer. Specifically, perioperative complications are more likely to occur in patients receiving preoperative irradiation. We examined the perioperative complications associated with TES in patients receiving preoperative irradiation.MethodsSeventy-seven patients underwent TES between May 2010 and April 2013. We performed a retrospective review of pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 15 publications
0
32
1
1
Order By: Relevance
“…27 In another study from the group of Tomita, 10 patients with spinal metastases for which en bloc spondylectomy was performed, had no recurrences after 10 years of follow up. 28 Complication rates for en bloc spondylectomy vary widely 14,24,29,30 and partially depends on surgeons' caseload and expertise. Whether more radical surgical removal of metastatic spinal lesions affects survival is unclear; a different question is whether en bloc resection might lower the rate of LLC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In another study from the group of Tomita, 10 patients with spinal metastases for which en bloc spondylectomy was performed, had no recurrences after 10 years of follow up. 28 Complication rates for en bloc spondylectomy vary widely 14,24,29,30 and partially depends on surgeons' caseload and expertise. Whether more radical surgical removal of metastatic spinal lesions affects survival is unclear; a different question is whether en bloc resection might lower the rate of LLC.…”
Section: Discussionmentioning
confidence: 99%
“…While it is thought that radical en bloc resections may reduce the incidence of loss of local control, 9 such interventions are associated with higher surgical risks. 14 The reported incidence of loss of local control after piecemeal intralesional debulking varies between 1.4 and 32% depending on the definition used for loss of local control: 32% for radiological loss of local control, 15 20-22% for symptomatic loss of local control 16,17 and 1.4-8.4% for patients effectively undergoing revision surgery. 18,19 Laufer et al reported a median survival of 9 months after repeat surgery for recurrent spinal metastasis, and a 65% rate of preserved ambulation.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies at our facility, occurrence of intraoperative dural injury was significantly higher at ≥12 months postirradiation than at <12 months [ 12 ]. In these cases, epidural fibrosis, as a late-stage radiation injury, could be a major cause of the subsequent dural injury.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is anticipated that meningeal permeability would be increased in association with postirradiation ABC thinning by a similar mechanism. Clinically, postoperative CSF leakage is sometimes experienced despite the absence of dural injury [ 12 ]; the possibility that this would be caused by an increase in meningeal permeability due to radiation injury is fully conceivable. In the future, analysis of more samples and experimental verification of increased meningeal permeability associated with ABC thinning is necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation